The lost city of Faar / 2. - MacHale, D. J. (Pendragon, 2003)
Fourteen-year-old Bobby Pendragon, apprentice to his Uncle Press, a Traveler responsible for solving interdimensional conflict, tries to locate the legendary lost land of Faar which may hold the key to the survival of the water-covered territory of Cloral, which stands on the brink of war.